Pengaruh Fluktuasi IHSG, Inflasi Dan Suku Bunga Terhadap Imbal Hasil Unitlink Berbasis Saham - Teguh Antolis; Samuel Dossugi (Journal of Applied Finance & Accounting, 2008)
Investment is a general word and is understood by the general society, but how to manage an investment or how to invest the money that will generate good return with small risk is an  attractive challenge and not known by many people. This paper will discuss about unit link, a newly developed investment instrument, which is predicted to be the new star for investment, together with the factors that influence the return of a unit link investment. Unit link is an innovation from the financial industry, and is a combination of insurance and investment. Year 2007 is the year where the stock market had a spectacular growth and this paper will discuss the IHSG fluctuation phenomenon, inflation and interest rate toward the equity-based unit link return and the effect of each factors. From the result of research, we can conclude that IHSG, inflation and interest will affect the equity-based unit link return where the most significant effect is shown by IHSG.